The broken chain: Evidence against emotionally driven upstream indirect reciprocity - Schnedler, Wendelin (Games and Economic Behavior)
Psychologists claim that being treated kindly puts individuals in a positive emotional state: they then treat an unrelated third party more kindly. Numerous experiments document that subjects indeed ‘pay forward’ specific behavior. For example, they are less generous after having experienced stinginess. This, however, is not necessarily driven by emotions. Subjects may also imitate what they regard as socially adequate behavior. Here, I present an experiment in which imitation is not possible at the next opportunity to act with a stranger: after being given either a fun or an annoying job, subjects have to decide whether to be generous or not. I find that although subjects who are given the annoying job report more negative emotions than those with the fun job, they do not treat an unrelated third person more unkindly in terms of passing on less money.
Keywords: Economics and Econometrics; Finance

Against All Odds: Tentative Steps Toward Efficient Information Sharing in Groups - Schlangenotto, Darius; Schnedler, Wendelin; Vadovic, Radovan (Games)

Revisiting a Remedy Against Chains of Unkindness - Schnedler, Wendelin; Stephan, Nina Lucia (Schmalenbach Business Review)

Don't patronize me! An experiment on preferences for authorship - Lübbecke, Silvia; Schnedler, Wendelin (Journal of Economics & Management Strategy)

"Cheap Talk with Multiple Strategically Interacting Audiences: An Experimental Study" - Li, Xinyu; Peeters, Ronald ("Cheap Talk with Multiple Strategically Interacting Audiences: An Experimental Study")

Playing hard to get: an economic rationale for crowding out of intrinsically motivated behavior - Schnedler, Wendelin; Vanberg, Christoph (European Economic Review)

Legitimacy of Control - Schnedler, Wendelin; Vadovic, Radovan (Journal of Economics and Management Strategy)

Uncertainty aversion and Preferences for Randomization: An Experimental Study - Schnedler, Wendelin; Dominiak, Adam (Economic Theory)

Too Few Cooks Spoil the Broth: Division of Labour and Directed Production - Schnedler, Wendelin; Ratto, Marisa (The B.E. Journal of Economic Analysis & Policy)

When is it Foolish to Reward for A while Benefiting from B - Schnedler, Wendelin (Journal of Labor Economics)